AKTIVITAS EKSTRAK ETANOL 96% KULIT BIJI MELINJO (Gnetum gnemon) SEBAGAI ANTIBAKTERI Salmonella enteritidis - Ade Kusmiati; Tri Saptari Haryani; Triastinurmiatiningsih . (Universitas Pakuan, 2019)
Salmonella enteritidis contamination in chicken meat causes chicken meat to rapidly decay. The use of chemical preservatives is very harmful, therefore the use of natural materials is recommended because it is safer to consume for humans. One of them is using Melinjo seed skin which has antibacterial power. The purpose of the study is to find out the activity of Melinjo seed bark extract (Gnetum gnemon) in inhibiting the growth of Salmonella enteritidis that can be used as a natural preservative in chicken meat. The first stage of the study was by extracting Melinjo seed bark using ethanol 96% with maceration method for 6 days. Activity test of Melnjo seed bark extract against Salmonella enteritidis using method of disc paper with a variation of the treatment of 25%, 50%, 75% and tetracycline positive control. The observed parameter is the measurement of the inhibited region Diameter (DDH) and the phytochemical test against Melinjo seed bark extract. The research results for the testing of the area Diameter of the hhibited region obtained the most effective concentration of 75% in the diameter of the area of the barrier of 10.3 mm and categorized with antimicrobial power levels of moderate sensitivity as well as can be used as natural preservatives in chicken meat. Phytochemical test results indicate the presence of compound flavonoids, tannins, saponins and triterpenoid.